Zero-CAPEX strategy for implementing solar rooftop initiatives in Malaysia: towards a sustainable campus - Mohd Abbas, Norliana; Abd Razak, Azli; Mohamad, Mohd Faizal; Nazli, Siti Nurshahida; Mazlan, Ain Syuhada; Abdul Khalid, Ezham (UiTM Press, 2025)
This study provides the first comprehensive empirical assessment of Zero Capital Expenditure (Zero-CAPEX) financing strategies for solar photovoltaic (PV) implementation in Malaysian higher education institutions, specifically addressing the critical barrier of substantial upfront investment costs that significantly impede renewable energy adoption across the sector. Using a robust mixed-methods approach that combines qualitative financing assessment with quantitative energy performance evaluation, the research examined solar PV operations across three Universiti Teknologi MARA (UiTM) campuses operating under Net Energy Metering (NEM) schemes during a four-month operational validation period from June to September 2021. The performance analysis demonstrated remarkable energy consumption reductions averaging 503,054 kWh across all campuses, substantially exceeding the initially projected 25% reduction targets, with Campus B achieving an exceptional 70% reduction in energy consumption. Detailed Net Present Value (NPV) calculations revealed consistently positive financial returns ranging from RM 2,189,850 to RM 3,403,936 over the complete 21-year contract period, demonstrating robust long-term profitability for both educational institutions and private investors. Campus-specific energy reductions of 389,500 kWh (Campus A), 514,219 kWh (Campus B), and 605,445 kWh (Campus C) effectively validated Zero-CAPEX model effectiveness under Malaysian tropical environmental conditions. The research establishes NEM as the optimal Zero-CAPEX framework for educational institutions, providing concrete empirical evidence of both technical feasibility and economic sustainability. Comprehensive sensitivity analysis incorporating varying tariff escalation scenarios (2-2.9% annually) confirmed the model's robustness, with higher utility rates further strengthening the Zero-CAPEX value proposition and financial attractiveness for stakeholders.